The Evolution of the Hallmarks of Aging - Lemoine, Maël (Frontiers in Genetics, 2021)
The evolutionary theory of aging (ETA) has set the foundations for a comprehensive understanding of aging. The biology of aging has listed and described the “hallmarks of aging,” i.e., cellular and molecular mechanisms involved in human aging. The present paper is the first to infer the order of apparition of the hallmarks of human aging throughout evolution from their presence in progressively narrower clades. Its first result is that all organisms, even non-senescent, have to deal with at least one mechanism of aging – the progressive accumulation of misfolded or unstable proteins. The other hallmarks are called “layers of aging.” A difference should be made between the first four layers of unicellular aging, present in some unicellular organisms and in all multicellular opisthokonts, that stem and strike “from the inside” of individual cells and span from increasingly abnormal protein folding to deregulated nutrient sensing, and the last four layers of metacellular aging, that progressively appeared in metazoan, strike the cells of a multicellular organism “from the outside,” that is because of other cells, and span from transcriptional alterations to the disruption of intercellular communication. The evolution of metazoans and eumetazoans had first succeeded in uncapping the limitation to potential lifespan due to unicellular aging. However, metacellular aging originates in the mechanisms by which the effects of unicellular aging are kept under control – e.g., the exhaustion of stem cells that contribute to replace damaged somatic cells. In bilaterians, additional functions have taken a toll on generally useless potentially illimited lifespan to increase the fitness of organisms at the price of a progressively less efficient containment of the damage of unicellular aging. In the end, this picture suggests that geroscience should be more efficient in targeting conditions of metacellular aging rather than unicellular aging itself.